INTERPROFESSIONAL COLLABORATION IN HIGH-COMPLEXITY UNITS: CHALLENGES, TEAM PERCEPTIONS, AND IMPACTS ON QUALITY AND SAFETY OF CARE - Ferreira, Brayan Almeida; Alves, Elda Lenilma Palheta; da Silva, Luiz Alberto Fernandes; do Vale, Júnio Fábio Silva; Pereira, Cíntia Anjos Braga; Costa, Maria de Fátima Freire; dos Santos, Uiliam Florentino; Araújo, Amanda Martins; do Nascimento, Aline Martins Araújo; de Almeida, Bruno Nunes; Carretilha, Arilana de Jesus; Santos, Julio Gladston Ribeiro; et al. (Seven Editora, 2025)
Interprofessional collaboration is a fundamental component for care quality and patient safety in high-complexity settings such as Intensive Care Units (ICU) and emergency services. This study, conducted through a narrative literature review, aimed to analyze the challenges, professional perceptions, and impacts of collaborative practice in these environments. The search was carried out in the BVS, LILACS, SciELO, and related institutional repositories, resulting in more than 15 publications addressing interprofessional communication, teamwork, patient safety, and collaborative strategies. The findings show that structured communication, clarity of professional roles, and continuous interaction among team members are key factors for effective collaboration. Integrated practices were found to prevent adverse events, enhance therapeutic accuracy, strengthen institutional protocols, and improve clinical outcomes. However, barriers such as professional hierarchy, communication failures, work overload, and organizational limitations still hinder the consolidation of interprofessional practice. The study concludes that investing in collaborative culture, interprofessional education, and institutional integration strategies is essential to promote safe, humanized, and efficient care in high-complexity hospital settings. DOI: https://doi.org/10.56238/sevened2025.037-042